2005
DOI: 10.1111/j.1365-3059.2005.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Erwinia amylovora strains from different host plants through RFLP analysis and sequencing of hrpN and dspA/E genes

Abstract: A total of 73 Erwinia amylovora strains obtained from 13 Maloideae host species and from Rubus spp., and isolated from different geographic areas, were assessed using RFLP and DNA sequencing analysis of the 3 ′ hrp N gene and /or of a fragment of 1341 bp of the dsp A/E region. An Erwinia pyrifoliae strain, used as outgroup, was checked in the same way. For the three strains isolated from Rubus spp. and for one strain from Amelanchier sp., RFLP analysis of the hrp N gene using the Rsa I enzyme yielded a PCR pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…The sequence homology with other E. amylovora strains from P. communis was 99%. The difference of this strain was also pointed out by pathogenicity tests and by assessing and comparing genes involved in the pathogenicity of E. amylovora such as hrpN and dspA/E (Giorgi and Scortichini 2005). By using AFLP, Rico et al.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence homology with other E. amylovora strains from P. communis was 99%. The difference of this strain was also pointed out by pathogenicity tests and by assessing and comparing genes involved in the pathogenicity of E. amylovora such as hrpN and dspA/E (Giorgi and Scortichini 2005). By using AFLP, Rico et al.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated very limited cross‐infectivity between Spiraeoideae‐ and Rubus ‐infecting isolates of E. amylovora : Rubus isolates are mostly unable to cause fire blight symptoms when inoculated into apple trees or immature pear fruits, whereas Spiraeoideae‐infecting isolates generally elicit a limited local response in raspberry when administered at high doses (Braun and Hildebrand, 2005; Evans, 1996; Giorgi and Scortichini, 2005). Nonetheless, cross‐infected isolates survive on and can be recovered from the nonhost plant, whilst maintaining their ability to infect their original host (Braun and Hildebrand, 2005; Evans, 1996; Giorgi and Scortichini, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The sequences of the gene were almost identical in European strains (Jock and Geider 2004). A study by Giorgi and Scortichini (2005) on E. amylovora isolates originating from different continents confirmed that there was a greater variation in the gene hrpN of bacteria isolated in North America where fire blight was discovered and described for the first time in the world. RFLP analysis of genes hrpN and dspA/E revealed significant differences between the strains isolated from plants of Rubus and Amelanchier, and those from the plants belonging to the family Maloidae (Giorgi and Scortichini 2005).…”
Section: Ribotypingmentioning
confidence: 58%
“…A study by Giorgi and Scortichini (2005) on E. amylovora isolates originating from different continents confirmed that there was a greater variation in the gene hrpN of bacteria isolated in North America where fire blight was discovered and described for the first time in the world. RFLP analysis of genes hrpN and dspA/E revealed significant differences between the strains isolated from plants of Rubus and Amelanchier, and those from the plants belonging to the family Maloidae (Giorgi and Scortichini 2005). Restriction fragment analysis of amsB gene (involved in the production of specific polysaccharide of E. amylovora-amylovoran) showed no differences between strains isolated in Poland (Puławska et al 2006).…”
Section: Ribotypingmentioning
confidence: 92%